Marcel's masterpiece : how a toilet shaped the history of art - Mack, Jeff (Henry Holt and Company, 2022)
"This is the story of Marcel Duchamp and how the Dada art movement changed the way people thought about what art could be and what could be art. From drawing a mustache on the Mona Lisa to attaching a bicycle wheel to a stool, Duchamp challenged long-held notions of art and how it should be made. People were amused, confused, and sometimes offended, and that was just the way Marcel Duchamp liked it. With Marcel's Masterpiece, Jeff Mack explores Duchamp's most famous provocation, and asks readers to ponder the ideas that help us see the world in new and interesting ways." --Provided by publisher